Frameless robot-assisted stereoelectroencephalography-guided radiofrequency: methodology, results, complications and stereotactic application accuracy in pediatric hypothalamic hamartomas - Li, Ping; Zhou, Yuanfeng; Zhang, Qin; Yang, Yuantao; Wang, Min; Zhu, Renqing; Li, Hao; Gu, Shuo; Zhao, Rui (Frontiers in Neurology, 2023)
We aimed to investigate the methodology, results, complications and stereotactic application accuracy of electrode implantation and its explanatory variables in stereoelectroencephalographyguided radiofrequency thermocoagulation (SEEG-RFTC) for pediatric hypothalamic hamartoma.Children with hypothalamic hamartoma who underwent robot-assisted SEEG-RFTC between December 2017 and November 2021 were retrospectively analyzed. The methodology, seizure outcome, complications, in vivo accuracy of electrode implantation and its explanatory variables were analyzed.A total of 161 electrodes were implanted in 28 patients with 30 surgeries. Nine electrodes not following the planned trajectories due to intraoperative replanning were excluded, and the entry point and target point errors of 152 electrodes were statistically analyzed. The median entry point error was 0.87 mm (interquartile range, 0.50-1.41 mm), and the median target point error was 2.74 mm (interquartile range, 2.01-3.63 mm). Multifactor analysis showed that whether the electrode was bent (b = 2.16, P < 0.001), the length of the intracranial electrode (b = 0.02, P = 0.049), and the entry point error (b = 0.337, P = 0.017) had statistically significant effects on the target error. During follow-up (mean duration 31 months), 27 of 30 (90%) procedures were seizure-free. The implantation-related complication rate was 2.6% (4/152), and the major complication rate in all procedures was 6.7% (2/30).Robot-assisted SEEG-RFTC is a safe, effective and accurate procedure for pediatric hypothalamic hamartoma. Explanatory variables significantly associated with the target point localization error at multivariate analysis include whether the intracranial electrode is bent, the intracranial electrode length and the entry point error.